Respon Pertumbuhan Tanaman Sawi Pagoda (Brassica narinosa L.) dengan Pemberian Pupuk NPK dan Pupuk Cair dari Limbah Organik - Devi, Sherly Berliana; Rahmi, Hayatul; Rahayu, Yayu Sri (UNIVERSITAS LABUHANBATU, 2024)
Continuous use of inorganic fertilizers results in problems with soil quality. One solution to reduce this problem is the use of a combination of inorganic fertilizer and liquid fertilizer from organic waste. This research aims to obtain a combination of NPK fertilizer and liquid fertilizer from organic waste that has the best effect on the growth of pagoda mustard plants. The research method used was the single-factor randomized group design (RAK) experimental method. The factors tested were a combination of NPK fertilizer and liquid fertilizer from organic waste with 8 treatments, namely A (300 kg/ha NPK fertilizer + 0 ml/l liquid fertilizer from organic waste), B (0 kg/ha NPK fertilizer + 200 ml/ l liquid fertilizer from organic waste), C (200 kg/ha NPK fertilizer + 100 ml/l liquid fertilizer from organic waste), D (200 kg/ha NPK fertilizer + 200 ml/l liquid fertilizer from organic waste), E ( 200 kg/ha NPK fertilizer + 300 ml/l liquid fertilizer from organic waste), F (100 kg/ha NPK fertilizer + 100 ml/l liquid fertilizer from organic waste), G (100 kg/ha NPK fertilizer + 200 ml/ l liquid fertilizer from organic waste), H (100 kg/ha NPK fertilizer + 300 ml/l liquid fertilizer from organic waste). Consisting of 8 treatments and 5 replications. The results of the analysis of variance and DMRT level of 5% showed that the combination of NPK fertilizer and liquid fertilizer from organic waste had no significant effect on plant height or root length.Â Keywords: Pagoda mustard greens, NPK fertilizer, liquid fertilizer, organic waste